Serum soluble sialic acid‐binding immunoglobulin‐like lectin‐7 concentration as an indicator of liver macrophage activation and advanced fibrosis in patients with non‐alcoholic fatty liver disease. Issue 4 (26th December 2019) - Sakamoto, Yuzuru; Yoshio, Sachiyo; Doi, Hiroyoshi; Kawai, Hironari; Shimagaki, Tomonari; Mori, Taizo; Matsuda, Michitaka; Aoki, Yoshihiko; Osawa, Yosuke; Yoshida, Yuji; Arai, Taeang; Itokawa, Norio; et al.
Abstract : Aim: Non‐alcoholic fatty liver disease (NAFLD) is a leading cause of liver disease worldwide. Because liver fibrosis is associated with the long‐term prognosis of patients with NAFLD, there is an urgent need for non‐invasive markers of liver fibrosis. Sialic acid‐binding immunoglobulin‐like lectin‐7 (Siglec‐7) is an immunomodulatory molecule expressed on various immune cells, including macrophages, which plays a key role in liver inflammation and fibrosis in NAFLD. We aimed to determine whether serum levels of soluble Siglec‐7 (sSiglec‐7) could have utility at a marker of fibrosis in this patient population. Methods: We examined serum samples from 93 NAFLD patients and 19 healthy donors for macrophage‐associated protein, including sSiglec‐7, soluble CD163, and YKL‐40, and examined their correlation with liver fibrosis scores, tissue elastography, and histological findings. Independent factors associated with advanced fibrosis were analyzed using a logistic regression model and a decision tree. To clarify the source of sSiglec‐7, we examined its expression in liver tissue‐derived macrophages and cultured monocyte‐derived macrophages. Results: Serum sSiglec‐7 levels were significantly higher in NAFLD patients compared with healthy donors, and correlated positively with sCD163 and YKL‐40 levels. Serum sSiglec‐7 was an independent diagnostic marker with high specificity (96.3%) for advanced fibrosis (F3 and F4) in NAFLD patients. Siglec‐7 was mainly expressed on CCR2 + macrophages in the liver, and sSiglec‐7 production by monocyte‐derived macrophages in vitro was increased after stimulation by pro‐inflammatory factors. Conclusions: Elevated serum sSiglec‐7 could serve as an independent marker with high specificity for advanced liver fibrosis in patients with NAFLD.